An analysis of the relationship between body mass index (BMI) and handwriting skills in children aged 8 to 10 years - Madhat, Athraa Hussein (Adolescência e Saúde, 2025)
This study aims to analyze and evaluate the relationship between Body Mass Index (BMI) and writing skills among children in primary education, aged 8 to 10 years. It focused on analyzing the differences in demographic and physiological characteristics among four groups of children. The methodology relied on assessing the writing skills of a sample of 395 children with diverse demographic characteristics using approved assessment tools. Accuracy, speed, coordination, and pen control skills were assessed, and the regression relationship between these skills and BMI was studied. The results indicated a negative relationship between BMI and writing skills in general: the higher the BMI, the lower the writing skills. The results also showed that age, gender, and right- or left-handed pen use were not statistically significant variables, despite slight differences in age and the ratio of females to males. The correlation coefficient for the sample that underwent the experiment, which had an average BMI of 16.9 (i.e., between thinness and normal weight), had an average value of 55%. However, from the linear regression analysis, it became clear that the correlation coefficient reached 98%, indicating a strong negative correlation. As for the value of \(p = 0.038\), which is less than the threshold value of 5%, the results obtained are highly significant. The coefficient of variation was large, meaning that the data show statistical differences and significance that can explain the phenomenon. This emphasizes the need for deeper analysis to understand the factors associated with BMI and their impact on health and growth.